Analisis Pengaruh Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Septiana, Arrum; Zulkifli, Zulkifli (Jurnal Riset AKuntansi dan Bisnis, 2024)
This study analyzes the effect of profitability and leverage on company value with company size as a moderation variable in LQ45 Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique uses purposive sampling, so the total research sample is 83 companies. This research data was analyzed using multiple linear regression analysis and moderated regression analysis (MRA) technique with the help of SPSS software version 26. The results showed that profitability had a positive and significant effect on the value of the company. Leverage has a positive and significant effect on the value of the company. Company size cannot moderate the effect of profitability on company value, but company size can moderate the effect of leverage on company value.